A Legal Analysis of the Implementation of Social Assistance Policies in Indonesia: Challenges in Data Synchronization and Law Enforcement - Ramayanti Ramayanti; Holijah Holijah (Fakultas Syariah Universitas Islam Negeri Sultanah Nahrasiyah Lhokseumawe, 2026)
This study aims to analyze the implementation of social assistance policies in Indonesia from a legal perspective by examining the alignment between applicable legal regulations and their implementation in the field, particularly regarding the challenges of data synchronization and law enforcement mechanisms. The research method used is a normative legal approach through legislative, conceptual, and analytical methods, utilizing primary legal sources such as the 1945 Constitution of the Republic of Indonesia, Law No. 11 of 2009 on Social Welfare, and Law No. 13 of 2011 on the Handling of the Poor, supported by secondary and tertiary legal sources. The analysis was conducted qualitatively through content analysis and legal interpretation to identify the gap between legal norms (das sollen) and the reality of implementation (das sein). The research findings indicate that although social assistance policies in Indonesia have a strong constitutional and legal foundation, their implementation still faces various serious issues, such as inaccuracies in beneficiary data, regulatory disharmony between the central and local governments, weak administrative oversight, and suboptimal law enforcement regarding the misuse of social assistance. These conditions have prevented the principles of justice, legal certainty, transparency, and accountability from being fully realized. Therefore, it is necessary to strengthen regulatory harmonization, integrate the national social data system, and enhance oversight and the enforcement of both administrative and criminal laws in order to achieve social assistance policies that are more effective, targeted, fair, and accountable. This study contributes to the development of public policy law by emphasizing the importance of strengthening the legal aspects of social welfare governance in Indonesia.